2018
DOI: 10.1515/opag-2018-0039
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Fruit Biochemical Characteristics of Three Strawberry Genotypes under Different Potassium Concentrations of Nutrient Solution

Abstract: A nutrient solution experiment was performed to evaluate the growth, yield and fruit biochemical characteristics of strawberry under different potassium levels of nutrient solution. Potassium concentrations including 235 (control), 350, 450 and 600 mg L-1 were applied to three strawberry genotypes of Camarosa, Selva and Parus under hydroponic culture. In the three genotypes, the maximum leaf area was observed at 350 mg L-1 K, and the maximum shoot fresh weight was either at 350 mg L-1 (in Camarosa and Parus) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 18 publications
2
20
0
1
Order By: Relevance
“…Similar responses have been obtained when K is raised from 8 to 9 molc m -3 NS in tomato (Ramírez et al, 2012). In strawberries and pepper, increasing the K supply from 210 mg L -1 to 350 mg L -1 in the nutrient solution significantly increased key quality attributes of fruits (Tohidloo et al, 2018).…”
Section: β-Carotenesupporting
confidence: 72%
See 1 more Smart Citation
“…Similar responses have been obtained when K is raised from 8 to 9 molc m -3 NS in tomato (Ramírez et al, 2012). In strawberries and pepper, increasing the K supply from 210 mg L -1 to 350 mg L -1 in the nutrient solution significantly increased key quality attributes of fruits (Tohidloo et al, 2018).…”
Section: β-Carotenesupporting
confidence: 72%
“…Potassium (K) has key roles in various physiological and biochemical processes in plants, including photosynthesis, osmoregulation, enzyme activity, secondary metabolism, protein biosynthesis, sugar transport and many quality traits of products (Oosterhuis et al, 2014;Pourranjbari Saghaiesh et al, 2018;Tohidloo et al, 2018). Likewise, in open field tomato cultivation, K doses from 0 to 60 and 120 kg ha -1 , or K levels of 200 to 400 mg L -1 in the hydroponic solution, increase the content of vitamin C, sugars, lycopene, and protein of the fruit (Almeselmani et al, 2009;Ahmad et al, 2015), although decreases in sugars (42 to 25 g) and vitamin C were also reported due to a K supply of 0 to 200 kg ha -1 (Ehsan- Akhtar et al, 2010).…”
mentioning
confidence: 99%
“…El K es crucial para muchas reacciones bioquímicas que son esenciales para la activación de enzimas y los procesos fisiológicos en la célula (Anees et al, 2016). El tamaño, la apariencia, el color, los sólidos solubles, la acidez, el contenido de vitaminas, el sabor y la vida útil de la fruta están significativamente influenciados por un suministro adecuado de K (Tohidloo et al, 2018). Extracción de nutrientes por la fruta.…”
Section: Resultados Y Discusiónunclassified
“…The highest fruit sugar content was obtained from the treatment of 40 Mg/ha, which did not show a statistically significant difference with the level of 20 Mg/ha; the lowest sugar content was observed for the control treatment, which had no statistical difference from the level of 5 Mg/ha (Figure 5A,B). According to Tohidloo and Souri [58], plants use both active and passive mechanisms for the better uptake of B. However, under deficiency of B, xylem uptake is the most common pathway.…”
Section: Sugar Contentsmentioning
confidence: 99%